Qualitative research, quantitative research and beyond - Tonelli, Maria José (2018)
The recent paper of Cassel (2018) on the similarities between the skills required to conduct qualitative research and to perform management functions has rekindeled an old debate about the contrast between qualitative and quantitative research. The author believes that MBA students conducting qualitative research for the first time acquire managerial skills such as the ability to analyze complex environments, which is a fundamental skill for organizations today. The study presents empirical data sourced from students and managers about the skills acquired in the research process.